KEANEKARAGAMAN TUMBUHAN HERBA DI SUNGAI PAYETI SEBAGAI MEDIA PEMBELAJARAN BIOLOGI BERBENTUK HERBARIUM - Putri Ronauli Sihombing; Erfy Melany Lalupanda; Yoin Meissy Matulessy (Universitas Lambung Mangkurat, 2024)
The purpose of this research is to know the diversity of plants and the use of plants as learning media in the form of a herbarium. This type of research is a descriptive ecological research with a quantitative approach. Based on the results of the research, it is known that the diversity of herbaceous plants in the Payeti River is classified as moderate with a value of H' = 2.703. Analysis of other ecological indices such as density is known to be the largest density by Digitaria setigera with a relative density value (KR) of 9.54% while the smallest density by Eleocharis geniculate which has a relative density value (KR) of 0.27%, the highest frequency is owned by Digitaria setigera which has a relative frequency value of 11.14% while Eleocharis geniculata has a low frequency species with a relative frequency value of 0.59% and a dominance index of herbaceous plants of 0.071 which is relatively low. The diversity of herbaceous plants was used as a learning medium in the form of a herbarium which obtained an average validation value of 95.06 and was classified as very valid.